Reliability of knee biomechanics during a vertical drop jump in elite female athletes - Mok, K.-M.; Petushek, E.; Krosshaug, T. (Gait and Posture, 2016)
The purpose of the study was to assess the within-session and between-session reliability of knee kinematics and kinetics in a vertical drop jump task among elite female handball and football athletes. Specifically, we aimed to quantify the within-session waveform consistency and between-session consistency of the subject ranking for a variety of knee kinematics and kinetics.